The Role of Citizenship in Promoting Social Integration and Community Welfare - Meldiya Zultita (International Journal of Students Education, 2024)
The role of citizenship is an essential foundation in the development of an inclusive and harmonious society. This research aims to examine the role of citizenship in promoting social integration and community welfare in Indonesia. The method used in this research is the library research method in the form of qualitative research. The results of this research show that the role of citizenship, social integration and community welfare play an important role in building an inclusive, harmonious and sustainable society. Effective citizenship education is necessary to develop awareness of shared responsibility and the values of inclusion. Challenges such as unequal access to resources, social conflict, technological developments, globalization and environmental problems are obstacles that must be overcome. To overcome this challenge, a comprehensive approach is needed that involves all stakeholders, including government, civil society, the private sector and international institutions. The strategies needed include strengthening civic education, efforts to reduce social and economic disparities, building dialogue between groups, inclusive use of technology, and environmental protection. With strong commitment and real action from all parties, society can achieve strong social integration and sustainable prosperity for all its members.